Paul Klee and primitive art - Pierce, James Smith (Garland, 1976)
Considers folk art, African, Oceanic and Precolumbian art, and children's drawings.
Zugl.: New York, Univ., Diss.
Keywords: Klee, Paul <1879-1940>; Klee, Paul -- 1879-1940; Art primitif; Art, Primitive; Naturvolk; Kunst; Hochschulschrift